2015
DOI: 10.5858/arpa.2014-0557-oa
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oncotype DX Recurrence Score by Histologic Types of Breast Carcinoma

Abstract: Although the numbers are small, our findings raise further awareness of the significance between histologic type and grade, and RS in breast cancer. In some special histologic types of breast cancer, particularly those considered to follow either an excellent or poor clinical course by histology alone, it is unclear whether the ODXRS results are as meaningful as in carcinomas of no special type. Further investigation with higher numbers and outcome data is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 28 publications
2
30
1
Order By: Relevance
“…Several studies have shown that histologic grade, ER/PR/HER2 status, and Ki‐67 proliferation index correlate well with RS. () Our data also show that the combination of TNM and biomarker status provides prognostic information comparable to the RS in over 99% of T1‐2N0, ER+/HER2− BCs. Of note, two invasive lobular BCs in the NYULMC cohort were T3N0, histologic grade 2, ER+/HER2− BCs and both had low RS (10 and 5, respectively).…”
Section: Discussionsupporting
confidence: 68%
“…Several studies have shown that histologic grade, ER/PR/HER2 status, and Ki‐67 proliferation index correlate well with RS. () Our data also show that the combination of TNM and biomarker status provides prognostic information comparable to the RS in over 99% of T1‐2N0, ER+/HER2− BCs. Of note, two invasive lobular BCs in the NYULMC cohort were T3N0, histologic grade 2, ER+/HER2− BCs and both had low RS (10 and 5, respectively).…”
Section: Discussionsupporting
confidence: 68%
“…The lack of a survival benefit from the receipt of adjuvant chemotherapy for early stage ILC observed in our study is also consistent with the known genomic characteristics of this histologic subtype. The 21‐gene RS is predictive of chemotherapy benefit for patients with ER‐positive/HER2‐negative breast cancer . Several studies have evaluated the RS for both IDC and ILC.…”
Section: Discussionmentioning
confidence: 99%
“…The 21-gene RS is predictive of chemotherapy benefit for patients with ERpositive/HER2-negative breast cancer. 19 Several studies have evaluated the RS for both IDC and ILC. In 2 separate, single-center studies that included 108 patients 4 and 120 patients 5 with classical ILC, no patient was categorized in the high-risk group.…”
Section: Value Of Chemotherapy For Ilc and Idc/marmor Et Almentioning
confidence: 99%
“…A number of studies have described the association of the RS with morphologic features and biomarker expression [3140]. To the best of our knowledge, only one study reported the RS results of special histologic subtypes known to have a favorable prognosis, but the data pertain to only five cases (four MCs and one TC) [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Most MCs (78.8%) in our study had a low RS with a mean RS of 13 ± 6, Although three of thirty-three (9.1%) patients with MC had lymph node micrometastases, the RS was low at ≤11 in all three tumors. The only other study reporting the RS of MC found that three of four MCs had an intermediate RS [39]. Recently, MC with a micropapillary growth pattern in >50% of the tumor has been described as a clinically more aggressive variant of MC with increased rates of lymphatic invasion and regional lymph node metastasis [49].…”
Section: Discussionmentioning
confidence: 99%